(untitled) (DAPesquisa, 2021)
This article arises from theoretical research on fashion creative figures. It presents the different figures and institutions considered apt and able to create fashion throughout history. This research is qualified as qualitative, descriptive, and bibliographic. The methodology was that of theoretical review, conducting a survey, analysis, and bibliographic interpretation of books, dissertations, and theses on the history of fashion, in order to identify and briefly describe various expert figures. The criterion adopted to raise and systematize the bibliography were the works of Lipovetsky (2007), Sant’Anna (2009), Riello (2013), Laver (2008), and Baldini (2005). Data was analyzed critically and the information was synthesized and organized in chronological order. As a result, one can identify that from the craft corporations (royal manufacturers) and the aristocratic figures (with an emphasis on queens), the field of fashion is guided by experts in defining the canons of beauty, style, and taste. Also, it is denoted that the late fashion industrialization process gave brands the legitimate role of creation, placing fashion designers at the center of product ideation and development activities. This industrialization finds its peak in the fast fashion phenomenon. Such a model of creation and production is strongly criticized, including those regarding the ’creative unsustainability’ of fashion designers. Thus, as a final consideration of this work, one may observe a return to authorial fashion, which is based on the uniqueness of the creator and subjectivity in his creative process.